2022
DOI: 10.1002/chem.202202103
|View full text |Cite
|
Sign up to set email alerts
|

C−H Activation of Inert Arenes using a Photochemically Activated Guanidinato‐Magnesium(I) Compound

Abstract: UV irradiation of solutions of a guanidinate coordinated dimagnesium(I) compound, [{(Priso)Mg} 2 ] 3 (Priso = [(DipN) 2 CNPr i 2 ] À , Dip = 2,6-diisopropylphenyl), in either benzene, toluene, the three isomers of xylene, or mesitylene, leads to facile activation of an aromatic CÀ H bond of the solvent in all cases, and formation of aryl/hydride bridged magnesium(II) products, [{(Priso)Mg} 2 (μ-H)(μ-Ar)] 4-9. In contrast to similar reactions reported for β-diketiminate coordinated counterparts of 3, these CÀ H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 67 publications
(56 reference statements)
1
10
0
Order By: Relevance
“…As one of the Mg centers is still easily accessible for substrate binding, II reacts readily with CO. Likewise, polarization of the Mg−Mg bond can be realized by coordination of two different ligands but this concept so far has been hardly explored [4,5] …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As one of the Mg centers is still easily accessible for substrate binding, II reacts readily with CO. Likewise, polarization of the Mg−Mg bond can be realized by coordination of two different ligands but this concept so far has been hardly explored [4,5] …”
Section: Introductionmentioning
confidence: 99%
“…Thus preventing immediate Mg−Mg coupling, the highly reactive radical can reduce benzene. Jones and coworkers showed that the reactivity of I or related Mg−Mg bound complexes can also be increased by irradiation with UV or blue light resulting in bond cleavage and radical formation [4,10] . Such highly reactive low‐valent (BDI)Mg⋅ radical species were also obtained in the form of a deep purple powder by ball‐milling in the solid state [11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent work showed that alkyl radicals could be derived from the mechanochemical interaction of alkyl halides with freshly generated magnesium surfaces to accomplish Minisci-type alkylation of pyrimidine derivatives . In line with this work, and inspired by the elegant studies of Wakefield and Jones that showed the formation of a transient pyridine radical species from the reduction of pyridine by a low-valent dimagnesium­(I) complex (Scheme c), we envisioned that a halogenide radical XMg• (X = Cl, Br, or I) and/or dimagnesium­(I) complex might be concurrently formed with alkyl radicals by milling of the Mg(0) and alkyl halides . The resulting magnesium­(I) species could reduce pyridine to form the C-4 pyridine radical, thus allowing radical–radical coupling with alkyl radicals to access 4-alkylpyridines regioselectively.…”
mentioning
confidence: 82%
“…Moreover, the dimagnesium(I) species could also promote regioselective photochemical activation of the aryl CÀ H bond of toluene and xylenes through radical mechanisms. [21] Although the crystal data for compound 5 is not good enough and there is severe disorder of the solvent molecules, the preliminary structure can be unambiguously obtained (Figure S15). NMR spectra also indicate the presence of the ortho-dehydrogenated toluene at 2.29, 2.30, 7.00-7.25 ppm (for 1 H) and 21.4, 126.5-141.9 ppm for 13 C NMR (Figure S5, S6).…”
Section: Insertion Of Carbodiimide Into the Mgà Mg Bondmentioning
confidence: 99%